The Object of Archaeology: From “Marbles” to the Archaeological Landscape - Özkaya, Belgin T.; Özkaya, İsmail Y. (Actual Problems of Theory and History of Art, 2018)
Although the history of antiquarianism and the antique object amongst its material of study go way back, with the emergence of modern archaeology and the modern museum in the 19th century antiquities, the objects of interest for a narrow circle of learned cognoscenti up to that time, gained mass appeal and were transformed into archaeological objects and museum displays. From bits and pieces of sacred and quotidian artifacts to intact tombs, from broken colossal statues to architectural fragments, everything that was ferociously dug by “early archaeologists,” often away from the museums they would be put on display, became archaeological objects. Building parts, architectural sculptures, structural and decorative elements, all of which were once parts of immovable wholes and specific locales have become free-floating “marbles” detached from their places and associated with the individuals who “discovered” them, as in the case of the (in)famous Elgin or Canning marbles, and were transported over long distances as portable artifacts to become objects of display in museums.In our paper we trace the changing nature of the archaeological object alongside conservation policies by dwelling on two distinct Anatolian examples, those of Lycia and Commagene. The southwestern region and ancient civilization of Lycia was “discovered” by British explorer Charles Fellows at the beginning of the 1840s whose persistent appeal to the trustees paid off with the transportation of substantial amount of material to the British Museum, which were known as Xanthian marbles back then. In contradistinction, although earlier explored by Karl Sester and Otto Puchstein and about to be excavated by Karl Humann, the Mount Nemrud, part of the southeastern Anatolian region of ancient Commagene, was taken over in 1883 by Osman Hamdi, the authoritative director of the Ottoman Imperial Museum who vehemently fought against the exportation of archaeological material outside Ottoman territory. How did these two different attitudes to ancient sites and the archaeological object impact the later histories of these sites? We also look at the current situation, particularly the details of the project developed by PROMET PROJE for Commagene.
Keywords: Commagene; Lycia; Mount Nemrud; modern museum; antiquarianism; early archaeology; archaeological landscape